BOOK REVIEW : Institutionalising Northeast Asia: Regional Steps Towards Global Governance - Amado Mendes, Carmen (Penerbit Universiti Sains Malaysia (USM Press), 2010)
This book describes the current situation of integration and cooperation in Northeast Asia (China, Taiwan, South Korea, the Korean Peninsula and Japan), considered as "the most heavily militarised region in the world" (p.1). With 19 chapters by different authors, it combines several approaches to the attempts to create regional institutions, arguing that this is a process that is still in its early stages. The theoretical part of the book defines institutionalism and regionalism and includes a comparison of institutionalisation in Northeast Asia and within the European Union, showing the importance of identity building and regional leadership. The chapters of Yoshinobu Yamamoto, Richard Higgott and Martina Timmermann, and Baogang He provide a framework for the empirical part of the book, which focus on different case studies and make recommendations related to Northeast Asia. There is a first section on history, ideas and identity, which starts with a question "Northeast Asian regionalism at a crossroads: Is an East Asian Community in sight?" In this chapter, Gilbert Rozman, argues that "a search for 'community' means recognition of the need to seek common values" and that "ignoring values in order to concentrate on economic integration does not offer a way forward. Instead, a joint effort in Northeast Asia should seek consensus on essential values for regionalism" (p. 96). Rozman offers some orientations on how to achieve that, rejecting a purely functionalist approach and favouring the awareness of historical and cultural differences.